Immune restoration disease complicating antiretroviral therapy in patients with HIV infection: Implications and solutions - French, M.; Price, Patricia (2008)
Antiretroviral therapy (ART) for HIV infection is increasingly being used in resource-poor countries. This has resulted in substantial improvements in the health and life expectancy of HIV patients in these countries, mainly as a result of immune reconstitution. However, the great majority of these patients are very immunodeficient when ART is begun and are susceptible to disorders of immune reconstitution. The most common disorder is immune restoration disease (IRD), which results from the restoration of pathogen-specific immune responses that cause immunopathology. Virtually any pathogen that can cause an opportunistic infection can provoke IRD during immune reconstitution. Mycobacterium tuberculosis. Cryptococcus neoformans, HBV and HCV are the most significant pathogens. IRD of the CNS is often complicated by permanent neurological disability or death. Research on the immunopathogenesis of IRD is required to develop laboratory investigations that will assist in the diagnosis and prevention of IRD. © 2008 Future Medicine Ltd.